2022
DOI: 10.11591/ijece.v12i3.pp2996-3004
|View full text |Cite
|
Sign up to set email alerts
|

Automatic recognition of Arabic alphabets sign language using deep learning

Abstract: <span>Technological advancements are helping people with special needs overcome many communications’ obstacles. Deep learning and computer vision models are innovative leaps nowadays in facilitating unprecedented tasks in human interactions. The Arabic language is always a rich research area. In this paper, different deep learning models were applied to test the accuracy and efficiency obtained in automatic Arabic sign language recognition. In this paper, we provide a novel framework for the automatic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, they used a data augmentation approach to increase the model performance. It can also be seen that Duwairi et al [12] proposed VGGNET and obtained promising performance. Alani et al [45] achieved higher performance of 96.59 and 97.29% accuracy with and without the data augmentation approach, respectively.…”
Section: Comparative Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…However, they used a data augmentation approach to increase the model performance. It can also be seen that Duwairi et al [12] proposed VGGNET and obtained promising performance. Alani et al [45] achieved higher performance of 96.59 and 97.29% accuracy with and without the data augmentation approach, respectively.…”
Section: Comparative Analysismentioning
confidence: 88%
“…The results demonstrated that the Histogram of Oriented Gradients obtained promising performance, using One-Versus-All SVM and HOG identifiers. The Kinect sensor was used in [12] to develop a real-time automatic Arabic SL recognition system based on the Dynamic Time Warping coordination approach. Power and data gloves are not used by the software.…”
Section: Related Workmentioning
confidence: 99%
“…ArSL is difcult to recognize automatically; however, a new framework suggested by Duwairi and Halloush. [63] may help. Popular deep-learning models (such as AlexNet, VGGNet, and Inception Net) are used in this framework to do image processing through transfer learning.…”
Section: Related Workmentioning
confidence: 99%
“…Te study [34] also proposed a framework based on a variety of deep learning models for the automatic recognition of Arabic Sign Language, specifcally by using AlexNet, VGGNet, and GoogLeNet/Inception models in training and evaluating the efectiveness of shallow learning techniques using nearest neighbors and SVM algorithms as baselines. Te suggested algorithm provided encouraging results in detecting Arabic Sign Language with a 97% accuracy rate.…”
Section: Related Workmentioning
confidence: 99%